Hexane Extract of Rhizomes of Curcuma Longa, Zingiber Officinale and Curcumine Life Span Extension in Caenorhabditis Elegans By Reducing Fat in Intestine - Gazala, Parveen; Duraiswamy, Basavan; Ansari, Firoz (Med Phoenix, 2018)
Background: Curcumine is obtained from curcuma longa and we examined the effects of curcumin, hexane extracts of Curcuma longa and Zingiber officinale on the lifespan and aging in Caenorhabditis elegans and found that it responded to curcumin, hexane extracts of Curcuma longa and Zingiber officinale with an increased lifespan and reduced intracellular reactive oxygen species during aging.Methods: MutantStrains, culture, Curcumin and Hexane extract of Rhizomes of Curcuma longa and Zingiber officinale treatment of C. Elegan.Results: Curcumin and hexane extracts of Curcuma longa and Zingiber officinale increased the life span and life cycle of the N2 wild type and Zdls-5 worms. On comparison, curcumin was found to be the most effective followed by the hexane extracts of Curcuma longa and hexane extracts of Zingiber officinale. Hexane extracts of Zingiber officinale were found to be least effective. Sudan black staining exhibited that stored contents of fat in C.elegans decreased as the concentration of the drug increased.Conclusions: Our study has established that curcumin and hexane extract of rhizomes of Curcuma longa and Zingiber officinale provides longevity and decreases the fat content in C.elegans.Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 21-28